Sequential electrocoagulation and Fenton/Photo-Fenton processes for the treatment of membrane bioreactor effluent of landfill leachate - Kosem, Ebru; Ersoz, Oyku Nur; Yilmaz, Rabia Nefise; Babaoglu, Deniz; Guvenc, Senem Yazici; Can-Guven, Emine; Varank, Gamze (ELSEVIER, 2024)
Membrane Bioreactor (MBR) effluents can be characterized by high concentrations of resistant organic compounds and suspended solids. To improve the performance of advanced oxidation processes such as the Fenton and Photo -Fenton processes applied for resistant organic matter degradation, electrocoagulation (EC) was applied for effective suspended solids removal from leachate MBR effluent. In the EC process, the Al anode was combined with alternative cathodes (Al, Stainless Steel (SS), Gr, Ti), and the Al -SS anode -cathode combination was selected since it was the most effective combination based on chemical oxygen demand (COD) removal efficiency and specific energy consumption (SEC). The EC process parameters were optimized by Box-Behnken Design and 72.5% COD, 82.5% TSS, 71.1% UV 254 , and 92.5% color removal was obtained with the SEC value of 2.01 kWh/kg COD under optimum conditions (pH 6.87, current density 120 A/m 2 , and reaction time 17.3 min). Following the EC process, the Fenton and Photo -Fenton processes were conducted separately. Under the optimum conditions determined by conventional optimization; 71.9% COD, 90.3% color, 79.5% TSS, and 87.8% UV 254 removal efficiencies were obtained by the Fenton process whereas 75.1% COD, 93.3% color, 82.0%, TSS and 89.8% UV 254 removal efficiencies were obtained by the Photo -Fenton process. Total %92.3 and %93.1 COD removal efficiency were achieved by sequential EC -Fenton and EC -Photo -Fenton processes, respectively, and the final COD concentrations were 381 mg/L and 340 mg/L. Sequential separation -degradation processes showed good performance in the treatment of leachate MBR effluent and could be applied to the treatment of similarly characterized wastewater.
Keywords: Box-Behnken Design; Electrocoagulation; Fenton; Leachate; Photo-Fenton; WASTE-WATER TREATMENT; ELECTRO-FENTON; ELECTROCHEMICAL OXIDATION; CHEMICAL COAGULATION; ALUMINUM ELECTRODES; PILOT-SCALE; REMOVAL; IRON; OPTIMIZATION; Chemistry